2019
DOI: 10.2147/jpr.s196501
|View full text |Cite
|
Sign up to set email alerts
|

<p>Erector spinae plane block for postoperative analgesia in patients undergoing total abdominal hysterectomy: a randomized controlled study original study</p>

Abstract: Background: Abdominal hysterectomy is associated with marked postoperative pain and morbidity, but effective postoperative analgesia provides early recovery and ambulation. Aim: We intended to assess the efficacy of bilateral erector spinae plane block (ESPB) on postoperative analgesia in females undergoing abdominal hysterectomy under general anesthesia. Settings and Design: The design was a prospective, randomized, controlled, single-blind clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 31 publications
3
52
0
Order By: Relevance
“…In a study by Tulgar et al, 22 the analgesic effect of ESPB extended for 17, 13, and 16 hrs in three patients undergoing multiple abdominal procedures. In a recent study by Hamed et al, 24 the analgesic effect of ESPB extended for 12 hrs in patients undergoing total abdominal hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Tulgar et al, 22 the analgesic effect of ESPB extended for 17, 13, and 16 hrs in three patients undergoing multiple abdominal procedures. In a recent study by Hamed et al, 24 the analgesic effect of ESPB extended for 12 hrs in patients undergoing total abdominal hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…18 Further publications described its use for abdominal surgeries such as ventral hernia repair, 19 abdominoplasty, 20 bariatric surgeries, 21 laparoscopic abdominal surgeries, 22 cesarean section 8,23 and total abdominal hysterectomy. 24 To assess the efficacy of ESPB in patients undergoing ventral hernia repair, Chin et al 19 performed the block at T7 TP in a cadaveric model and evaluated the degree of injectate distribution using a computed tomography scan. They reported that the injectate was distributed cranially to the upper thoracic levels and caudally to the L2-L3 transverse processes.…”
Section: Discussionmentioning
confidence: 99%
“…All RCTs [5][6][7][17][18][19][20][21][22][23][24][25] reported data on intravenous opioid consumption 24 h after surgery . Pooled analysis showed that ultrasound-guided ESPB was associated with a reduction of opioid 24h after surgery (-2.18, 95% CI -2.76 to -1.61; P<.00001; Fig2).…”
Section: Primary Outcomesmentioning
confidence: 99%
“…All RCTs [5][6][7][17][18][19][20][21][22][23][24][25] reported data on intravenous opioid consumption 24 h after surgery. Pooled analysis showed that ultrasound-guided ESPB was associated with a reduction of opioid 24 h after surgery (− 2.18, 95% CI − 2.76 to − 1.61; P < .00001; Fig.…”
Section: Primary Outcomesmentioning
confidence: 99%